A Reconfiguration Circuit to Boost the Output Power of a Partially Shaded PV String - Ali Faisal Murtaza; Hadeed Ahmed Sher (Energies, 2023)
An optical isolator circuit is developed to detect and dynamically relocate the photovoltaic (PV) module under partial shading. The suggested system control structure operates in two modes. Mode 1 governs the system at global maxima (GM) by tracing the power-voltage (PV) curve. Mode 2 detects and separates all the bypassed modules from a PV string/array by means of a decentralized control and stores its power in the battery. Simulations are performed on different shading patterns to verify the efficacy of the suggested system. The results showcase that the averaged harnessed power using the proposed circuit is 25.26% more than the total cross-tied (TCT) and series-parallel (SP) array configurations. The proposed circuit does not require complex gate driver circuits and large switch counts. The circuit is scalable and can be implemented on an “N × N” array.